2010
DOI: 10.1007/s10545-010-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and high incidence of hyperornithinemia‐hyperammonemia‐homocitrullinemia (HHH) syndrome in northern Saskatchewan

Abstract: Mutations in the SLC25A15 gene, encoding the human inner mitochondrial membrane ornithine transporter, are thought to be responsible for hyperornithinemia-hyperammonemia-homocitrullinemia (HHH) syndrome, a rare autosomal recessive condition. HHH syndrome has been detected in several small, isolated communities in northern Saskatchewan (SK). To determine the incidence of HHH syndrome in these communities, a PCR method was set up to detect F188Δ, the common French-Canadian mutation. Neonatal blood spots collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, it may be missed on newborn screening because some affected neonates may not show in the first days of life elevated plasma ornithine levels that can be detected by tandem mass spectroscopy [90]. Authors suggested that the typical rise of plasma ornithine levels occurs after the first few days of life when blood samples for newborn screening are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…However, it may be missed on newborn screening because some affected neonates may not show in the first days of life elevated plasma ornithine levels that can be detected by tandem mass spectroscopy [90]. Authors suggested that the typical rise of plasma ornithine levels occurs after the first few days of life when blood samples for newborn screening are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…These patients can exhibit behavioral abnormalities similar to ASD such as developmental delay, ataxia, spasticity, learning disabilities, cognitive deficits and/or unexplained seizures [57]. Rats treated with intracerebroventricular administration of homocitrulline are also observed to have disrupted brain redox status and energy metabolism [58], [59]. These observations suggest that elevated brain levels of homocitrulline are deleterious; however additional studies are needed to define the brain levels of homocitrulline and the potential role in the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Except for one variant ( SLC25A15 p.F188del), our calculated carrier frequencies correlated with published data. The SLC25A15 p.F188del variant is common in French‐Canadians with an extremely high carrier rate of 1 in 19 in an isolated northern Saskatchewan region . This variant is almost exclusively reported in French‐Canadian HHH patients and had not been reported in AJ individuals except for a 1 in 94 carrier rate in a small control group with less than 300 self‐reported AJ individuals.…”
Section: Discussionmentioning
confidence: 99%